Young British Muslims Identity, Culture, Politics and the Media. - Kabir, Nahid A. (Edinburgh : Edinburgh University Press, 2010)
Based on 216 in-depth interviews of Muslims in Britain, the book examines how British Muslim youths and young adults, 15-30 years old, define their identities, their values and their culture and whether these conflict either with those of their parents or with the dominant non-Muslim British culture.
COVER; Copyright; CONTENTS; TABLES AND FIGURES; ABBREVIATIONS; GLOSSARY; ACKNOWLEDGEMENTS; FOREWORD; INTRODUCTION: MY RESEARCH OBSERVATIONs; 1. THE IDENTITY DEBATE; 2. MUSLIMS IN BRITAIN: AN OVERVIEW; 3. THE RELIGIOUS AND CULTURAL DILEMMA; 4. TO BE OR NOT TO BE BRITISH; 5. IS THE MEDIA BIASED AGAINST MUSLIMS?; 6. THE NIQAB DEBATE; 7. INDIGNATION ABOUT THE PROPOSAL TO INCLUDE SHARIAH LAW IN BRITAIN; CONCLUSION: A HUMANITARIAN WAY FORWARD; BIBLIOGRAPHY; INDEX.
Print version record.
Includes bibliographical references and index.
Keywords: Muslims -- Great Britain -- Ethnic identity; Muslims -- Great Britain -- Social conditions; SOCIAL SCIENCE -- Sociology -- General; RELIGION -- Islam -- Rituals & Practice; Muslims -- Ethnic identity; Muslims -- Social conditions; Great Britain; Electronic books; Electronic books